Eficiência técnica e metatecnologia do semiárido cearense: modelo de metafronteira estocástica - Silva, Roberto Bruno Pessoa e (2017)
Compare the technical efficiency (TE) between the semi-arid and non-semi-arid regions of Ceará using the metafrontier (FM) approach developed by Battese and Rao (2002) and redefined by Battese et al. (2004) and O'Donnell et al. (2008). The analysis is developed using an output (agricultural production) technology and multi-inputs (capital, labor, land, input expenses and capital stock). The following tests were applied to choose the best model: technical lack of technical progress, absence of technical progress and existence of two regional borders. It is emphasized that the result of the stochastic frontier technical absence test does not confirm the technical progress in the non-semi-arid region, and there should be a broader investigation to determine the reasons for this. Thus, the average metatechnology for the semi-arid region of Ceará was 52%, that is, the maximum product used by its own combinations of factors of production is, on average, about 52% of the maximum production that could be produced (potential production) Using the same factors of production and technology available in the non-semi-arid region. Regarding the average levels of technical efficiency (TE *) to the metafrontier, the semiarid has 44% and the non-semi-arid 70%. In this way, the set of combinations of the inputs and products of the region are much less efficient than the non-semiarid region. It can be concluded that the non-semi-arid region of Ceará has, on average, greater technical efficiency compared to the meta-frontier.